Studi Tentang Keberadaan â€œTerminal Bayanganâ€ Sukun Banyumanik Kota Semarang - Nugraha, Bramantya Adi; ., Sulistyowati (Journal of Politic and Government Studies, 2018)
The study of the existence of "shadow terminal" Sukun Banyumanik Semarang City has a purpose to know why Terminal Shadow Bread can continue to survive until now. Shadow Terminal Sukun that can continue to survive must also be based on the interconnection between networks that have the same background. In addition, the other purpose is to find out what the government's efforts to handle the Shadow Branch Terminal, and whether there are people or groups that become a strong reason why Shadow Terminal Terminal able to survive. Research on shadow terminal problem in Sukun Banyumanik area of Semarang City, especially on this shadow terminal problem will use descriptive research type with mix method approach method. Approach mix methods, namely a research step by combining two forms of approach in research that is qualitative and quantitative.. The method of mix methods in this research using Sequential exploratory model. The activities at the Banyumanik Banyumanik Shadow Terminal Semarang City is one of the problems that have existed since a long time in the area. Shadow Branch Terminal Happened due to Semarang City government policy by the end of 2010 to close shadow terminals in the city. Shadow Branch Terminal takes place in areas that have been banned for stops or parakeets. disregard the government's rules. This activity certainly brings a bad impact for the face of Semarang City as the capital of Central Java . Keynote : Net Organization, Shadow Terminal, and Semarang City